Somatostatin Receptors in Merkel-Cell Carcinoma: A Therapeutic Opportunity Using Somatostatin Analog Alone or in Association With Checkpoint Inhibitors Immunotherapy. A Case Report - Guida, Michele; D'Alò, Alessandro; Mangia, Anita; Di Pinto, Federica; Sonnessa, Margherita; Albano, Anna; Sciacovelli, Angela; Asabella, Artor Niccoli; Fucci, Livia (Frontiers in Oncology, 2020)
Background: Merkel-cell carcinoma (MCC) is a rare, highly aggressive skin cancer typically involving elderly people. Surgery is usually the first treatment for primary tumor. In adjuvant setting, radiotherapy is effective in reducing local recurrence and in improving overall survival. Regarding advanced disease, systemic chemotherapy ended up disappointing results whereas antiPD1/antiPD-L1 immunotherapy recently gave relevant clinical benefits. Interestingly, about the half of MCC patients expresses high somatostatin receptors (SRs) to possibly represent a target for the therapeutic use of somatostatin analogs (SSAs). Nevertheless, SSAs have been little studied in MCC and cases treated with SSAs in association with checkpoint inhibitor immunotherapy have not been published yet. Case Report: We report the case of a 73-year-old man affected by metastatic MCC of right arm previously treated with surgery and adjuvant radio and chemotherapy. Three years later the patient presented loco-regional relapse involving lateral-cervical, mediastinal, and submandibular lymph nodes with high value of chromogranin A and neuron specific enolase. Due to the high expression of SRs at octreoscan and immunoistochemistry, patient started octreotide 30 mg i.m. every 28 days with a good control of disease for about 2 years. A widespread progression of disease was reported afterwards. The patient started the antiPD-L1 avelumab immunotherapy, only recently available in Italy, while still taking SSA. The patient showed an impressive regression of the disease after only four cycles of avelumab until complete remission. Conclusions: SSA could be a valid therapeutic option in patients with MCC with high SR expression. When combined with PD-1/PD-L1 immune-checkpoint inhibition, SSA is likely to enhance antiproliferative activity. Our case report provides the rationale to conduct a prospective trial and translational research to verify the efficacy and safety of combined SSA and checkpoint inhibitors for advanced MCC.